A constructive heuristic algorithm to Short Term Transmission Network Expansion Planning - Rider, Marcos J.; Garcia, Ariovaldo V.; Romero, Rubén [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2004)
In this paper a method for solving the Short Term Transmission Network Expansion Planning (STTNEP) problem is presented. The STTNEP is a very complex mixed integer nonlinear programming problem that presents a combinatorial explosion in the search space. In this work we present a constructive heuristic algorithm to find a solution of the STTNEP of excellent quality. In each step of the algorithm a sensitivity index is used to add a circuit (transmission line or transformer) to the system. This sensitivity index is obtained solving the STTNEP problem considering as a continuous variable the number of circuits to be added (relaxed problem). The relaxed problem is a large and complex nonlinear programming and was solved through an interior points method that uses a combination of the multiple predictor corrector and multiple centrality corrections methods, both belonging to the family of higher order interior points method (HOIPM). Tests were carried out using a modified Carver system and the results presented show the good performance of both the constructive heuristic algorithm to solve the STTNEP problem and the HOIPM used in each step.
Keywords: Algorithms; Electric lines; Electric loads; Electric transformers; Heuristic methods; Mathematical models; Matrix algebra; Nonlinear programming; Optimization; Planning; Problem solving; Sensitivity analysis; Set theory; Topology; Voltage control; Electric energy; Garver system; Higher order interior points method (HOIPM); Transmission network expansion planning (TNEP); Electric power transmission networks